109k views
0 votes
Simply 8y(y - 4) + 3y(y+2)

User Buron
by
6.1k points

1 Answer

7 votes

Greetings

Answer:

11y² - 26y


Explanation:

First, multiply everything in the first bracket by 8y:

8y x y = 8y²

-4 x 8y = -32y

8y²-32y

Next bracket, multiply everything by 3y:

3y x y = 3y²

3y x 2 = 6y

3y² + 6y

Now put both equations together:

3y² + 6y + 8y²-32y

Add the y²:

3y² + 8y² = 11y²

Add the y's

6y - 32y = -26y

So the simplified version is:

11y² - 26y


Hope this helps!

User Luten
by
5.8k points